Food Security, Nutritional Challenges, and Prevention of Target Organ Damage in Afghanistan - Azaraksh Abdul Hassib; Aliseena Yussufpur; Farzam Fraidoon (Cleanliness: Journal of Health Sciences and Medical Research, 2026)
Food security is a fundamental determinant of health and a critical factor in preventing chronic diseases and target organ damage. In Afghanistan, decades of conflict, economic instability, and climate-related crises have created severe food insecurity, limiting access to safe, nutrient-rich, and diverse foods. Insufficient nutrition contributes to malnutrition, micronutrient deficiencies, and unhealthy dietary patterns, which exacerbate metabolic dysregulation and organ impairment. This study employed a narrative literature review and secondary data analysis of publications between 2020 and 2025, sourced from PubMed, Scopus, Web of Science, and reports from the World Health Organization (WHO) and Food and Agriculture Organization (FAO). Evidence from epidemiological studies, systematic reviews, and global nutrition reports was synthesized to examine the biological and socio-economic mechanisms linking food insecurity to chronic disease and progressive organ damage. Findings indicate that food insecurity in Afghanistan is strongly associated with elevated risks of cardiovascular disease, chronic kidney disease, type 2 diabetes mellitus, and metabolic liver disorders. Dietary insufficiency, particularly low intake of micronutrients and reliance on energy-dense, nutrient-poor foods, contributes to oxidative stress, chronic inflammation, and metabolic dysfunction, accelerating structural and functional impairment in the heart, kidneys, liver, and brain. Vulnerable populations—including children, women, the elderly, and displaced households—are disproportionately affected. Strengthening Afghanistan’s food systems, expanding access to nutrient-rich foods, promoting balanced dietary patterns, and integrating nutrition-sensitive policies into chronic disease prevention strategies are essential to mitigate organ damage and improve long-term population health outcomes.